Tuberculosis Risk in Ankylosing Spondylitis, Other Spondyloarthritis, and Psoriatic Arthritis in Sweden: A Population‐Based Cohort Study. Issue 10 (4th September 2018) - de Vries, Mirjam K.; Arkema, Elizabeth V.; Jonsson, Jerker; Bruchfeld, Judith; Jacobsson, Lennart T. H.; Askling, Johan; ,
Abstract : Objective: Rheumatoid arthritis is a risk factor for tuberculosis (TB), particularly following treatment with biologic agents. Since these therapies are increasingly used in ankylosing spondylitis (AS), other types of spondyloarthritis (SpA), and psoriatic arthritis (PsA), we investigated the corresponding TB risks in these patients. Methods: We identified individuals with AS/SpA/PsA, and non‐AS/SpA/PsA comparators by linking Swedish national patient, population, TB, and rheumatology registers, and followed them for TB occurrence. Incidence rates were estimated for biologic‐naive and biologic‐exposed patients and the comparators. We calculated hazard ratios (HRs), adjusted for age, sex, and country of birth. Results: Included in this study were 38, 702 patients with AS/SpA/PsA, and 200, 417 persons from the general population. Among the patients, 11 active TB cases were identified, with an incidence rate (per 10 5 ) of 22 (95% confidence interval [95% CI] 8.3–59.2) for biologic‐exposed patients, 2.7 (95% CI 1.3–5.6) for biologic‐naive patients, and 2.4 (95% CI 1.8–3.3) for non‐AS/SpA/PsA comparators. The adjusted HR comparing biologic‐naive patients to the general population was 1.2 (95% CI 0.5–2.7), and 7.5 (95% CI 1.9–29) comparing biologic‐exposed to biologic‐naive patients. Conclusion: Biologic‐naive AS/SpA/PsA patients are not at an increased TB risk in Sweden. Following treatment with biologic agents, the risk increased, but the absolute TB risk was low.